2022
DOI: 10.31557/apjcp.2022.23.2.529
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Profile of p16 Immunopositive and HPV DNA PCR Positive Oral Squamous Cell Carcinoma in a Large Cohort of Indian Patients

Abstract: Background:The Indian subcontinent has the highest incidence of oral cavity squamous cell carcinoma in the world. The high incidence of tobacco chewing habit with or without smoking has been found to be the chief culprit. However in a minor subset of patients Human Papilloma Virus may play a role. Materials and Methods: A total of 800 cases of Oral squamous cell carcinoma were included in the study. The patients were given a questionnaire comprising of questions about demographic details and habits. The biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 29 publications
(38 reference statements)
2
16
1
Order By: Relevance
“…A study conducted by Belobrov et al in 2018 also showed that male (57%) had more p16 positivity than females (43%) (23). In contrast to our results Naz et al in 2022 found no significant association of p16 expression with gender of the patients (24).…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…A study conducted by Belobrov et al in 2018 also showed that male (57%) had more p16 positivity than females (43%) (23). In contrast to our results Naz et al in 2022 found no significant association of p16 expression with gender of the patients (24).…”
Section: Resultscontrasting
confidence: 95%
“…In accordance to our results, a study conducted by Agarwal et al, in 2021 found no significant association between grades of OSCC and p16 expression (25). In contrast to our results, a study conducted by Naz et al in 2022 showed that the most of the OSCC cases with p16 positivity were found in the moderately differentiated (79.5%) followed by well and poorly differentiated OSCC (24). CONCLUSION 1 p16 expression in various grades of OSCC showed no significance association.…”
Section: Resultssupporting
confidence: 77%
“…Thirty-one studies met the inclusion criteria, comprising 5007 patients with OCSCC from 24 different countries. Sixteen studies were from Asia [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], eight from Europe [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], two from Africa [ 43 , 44 ], two from South America [ 35 , 45 ], two from North America [ 46 , 47 ], and one from Asian Pacific [ 48 ]. The study size ranged from 17 patients in a study from Uganda [ 44 ] to 940 patients in the Netherlands [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies ( n = 112) reported the mean age of patients with HPV+ OCSCC varying from 53 to 63 years. Two studies reported that HPV+ OCSCC was significantly associated with a lower mean age than HPV-negative (HPV−) OCSCC ( n = 59) [ 38 , 41 ] while five studies found it statistically insignificant [ 24 , 27 , 28 , 30 , 45 ]. The mean age in HPV−OCSCC ranged from 57.5–64 years [ 37 , 38 , 41 , 45 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation